Propagation of English Cricket Bat Willow in Kashmir Valley - Keng, G. Q. (Indian Forester, 1957)
English Bat Willow has been introduced in the valley in the second decade of this century. The tree yields a wood, light in weight and elastic in nature. The cultivation of the species is done by raising the sets in a nicely prepared nursery and planting them out on moist well aerated and loamy soil, after having attained the ideal size. It takes 16 years for the tree to reach a girth of 48" fit for conversion in cricket bat blades of various qualities. Progressive attempts are being made to raise a good number of plantations on right technique to meet the entire demand of the "Kashmir Willows" and to make it compete with the imported willow.